Estudio del comportamiento del consumidor de ropa infantil en el mercado de la ciudad de Machala - Camacho Jimenez, Jimmy Oswaldo (2015)
This project was conducted with the aim of analyzing and identifying consumer behavior child Machala city through market research for that survey questions was made to the population to gather customer information to know he likes or rather in terms of models and designs children's clothing. This project helps determine what their needs and desires of consumers to define which companies to make the right to apply its commercial business decisions, this information from the public is used to create and design strategies that encourage consumers to visit and purchase products according to their preferences in clothing for children. The proposal is given according to research to develop strategies and activities that the company can implement in your business, taking into account each of the objectives to be reached through market research, according to the analysis is obtained as the surveys of the population of Machala because the market there is no specialized local or sections of products that the consumer needs is a model that can help the different companies involved in the marketing of children's clothing which may implement for growth, positioning and customer acquisition and increase the volume of sales for their companies, in conclusion Machala market is feasible for the implementation of new business, it is necessary to implement the recommendations and marketing strategies in order to it employed safely and can offer products that consumers prefer and need and benefit both the company and the customer.